Review Sistematis : Tantangan Pembelajaran E-learning Selama Pandemi Covid-19 pada Mata Pelajaran IPA Kelas VII di SMP - Bustanuddin; Dimas Aziza Bustanil (Journal of Pedagogy and Online Learning, 2022)
Learning during the Covid-19 pandemic is recommended to be carried out online, in order to reduce the impact of the spread of the SARS-CoV-2 virus. One of the supporting elements that can facilitate online learning is E-learning. The change in learning methods that were originally carried out face-to-face to online learning experienced several challenges in terms of the availability of qualified technology such as electronic devices in the learning process, internet networks, and the readiness of students and teachers to face online learning. In terms of students, the challenges they face start from an unstable internet network, inadequate internet quota and the unavailability of gadgets for learning, resulting in a lack of students' understanding of the subject matter provided.